Reduction of kinesin I heavy chain decreases tau hyperphosphorylation, aggregation, and memory impairment in Alzheimer’s disease and tauopathy models - Selvarasu, Karthikeyan; Singh, Abhay Kumar; Iyaswamy, Ashok; Gopalkrishnashetty Sreenivasmurthy, Sravan; Krishnamoorthi, Senthilkumar; Bera, Amal Kanti; Huang, Jian-Dong; Durairajan, Siva Sundara Kumar (Frontiers in Molecular Biosciences, 2022)
Many neurodegenerative diseases, such as Alzheimer’s disease (AD) and frontotemporal dementia with Parkinsonism linked to chromosome 17, are characterized by tau pathology. Numerous motor proteins, many of which are involved in synaptic transmission, mediate transport in neurons. Dysfunction in motor protein-mediated neuronal transport mechanisms occurs in several neurodegenerative disorders but remains understudied in AD. Kinesins are the most important molecular motor proteins required for microtubule-dependent transport in neurons, and kinesin-1 is crucial for neuronal transport among all kinesins. Although kinesin-1 is required for normal neuronal functions, the dysfunction of these motor domains leading to neurodegenerative diseases is not fully understood. Here, we reported that the kinesin-I heavy chain (KIF5B), a key molecular motor protein, is involved in tau homeostasis in AD cells and animal models. We found that the levels of KIF5B in P301S Tau mice are high. We also found that the knockdown and knockout (KO) of KIFf5B significantly decreased the tau stability, and overexpression of KIF5B in KIF5B-KO cells significantly increased the expression of phospho and total tau levels. This suggested that KIF5B might prevent tau accumulation. By conducting experiments on P301S Tau mice, we showed that partially reducing KIF5B levels can reduce hyperphosphorylation of the human tau protein, formation of insoluble aggregates, and memory impairment. Collectively, our results suggested that decreasing KIF5B levels is sufficient to prevent and/or slow down abnormal tau behavior of AD and other tauopathies.